Numerical investigation on effect of blade shape for stream water wheel performance - A. N., Oumer; Azizuddin, Abd Aziz; Noor Azirhan, Sahat (IOP Publishing, 2018)
Stream water wheels are one of the oldest and commonly used types of wheels for the production of energy. Moreover, they are economical, efficient and sustainable. However, few amounts of research works are available in the open literature. This paper aims to develop numerical model for investigation of the effect of blade shape on the performance of stream water wheel. The numerical model was simulated using Computational Fluid Dynamics (CFD) method and the developed model was validated by comparing the simulation results with experimental data obtained from literature. The performance of straight, curved type 1 and curved type 2 was observed and the power generated by each blade design was identified. The inlet velocity was set to 0.3 m/s static pressure outlet. The obtained results indicate that the highest power was generated by the Curved type 2 compared to straight blade and curved type 1. From the CFD result, Curved type 1 was able to generate 0.073 Watt while Curved type 2 generate 0.064 Watt. The result obtained were consistent with the experiment result hence can be used the numerical model as a guide to numerically predict the water wheel performance.